Quantification of aerobic determinants of performance in post-pubertal adolescent middle-distance runners - Richard Blagrove; Glyn Howatson; Charles R. Pedlar; Philip R. Hayes (2019)
PURPOSE: The use of oxygen cost ([Formula: see text]aero) parameters to predict endurance performance has recently been criticized. Instead, it is suggested that aerobic energy cost ([Formula: see text]) provides greater validity; however, a comparison of these quantification methods has not previously been made. METHODS: Fifty-six male (n = 34) and female (n = 22) competitive adolescent (17 ± 1 years) middle-distance runners participated in a sub-maximal and maximal incremental treadmill test. Running economy (RE) was measured at the speed corresponding to lactate turnpoint, and the three speeds prior. Maximal oxygen uptake ([Formula: see text]O2max), speed at [Formula: see text]O2max and fraction of [Formula: see text]O2max utilized across a range of intensities, and speeds from 0.8, 1.5 and 3 km races were also quantified. RE and fractional utilization were calculated in units of [Formula: see text]aero and [Formula: see text]aero. RESULTS: Multiple linear regression models demonstrated no discernible difference in the predictive capability of RE, fractional utilization and [Formula: see text]O2max when expressed as [Formula: see text]aero or [Formula: see text]aero in both sexes. When plotted as a function of running speed, [Formula: see text]aero displayed a stepwise decrease (F = 11.59, p